Impact of a ball regulation change on game performance and shooting play in Japanese U-15 girls` handball - Nakayama, S.; Trejo-Silva, A.; Gomez-Ruano, M. A.; Aida, H. (Perceptual and Motor Skills, 2024)
We aimed to investigate how a ball regulation change, implemented in U15 girls` handball games, now affects game performance and shooting plays. Over 14 matches (28 observations), we included all the attacks (n = 813) and shooting plays (n = 589) with the conventional ball and all the attacks (n = 821) and shooting plays (n = 618) with the new ball performed by both teams. We used notational analysis to compare the game performance and shooting plays in these two conditions. Our main results were as follows: (i) the attack efficacy was higher with the new ball (41.9%) than with the conventional ball (36.1%); and (ii) the prevalence of the three-line defensive system was higher with the new ball (10.5%) than with the conventional ball (2.7%). It can be inferred that the new ball enabled backcourt players to execute more powerful middle- and long-range shots, leading to their adoption of deeper defensive tactics that were effective in halting advancing backcourt players. Moreover, implementing new ball regulations resulted in a significantly higher frequency of shots targeted at the upper third of the goal frame (44.4%) compared to those observed with the conventional ball (35.8%). This implies that the introduction of the new ball enhanced precision control over shot placements, resulting in an increased player preference for targeting the upper course. Lastly, goalkeepers` saving rates decreased under the new ball, highlighting the need for technical and tactical coaching, tailored to goalkeepers. In summary, implementing the new ball regulations had a positive impact on Japanese U15 girls` handball performance.